STUDENTS' INITIAL UNDERSTANDING OF THE CONCEPT OF CONSERVATION OF AREA - Rindu Alriavindrafunny (Journal on Mathematics Education, 2014)
The first idea that must be understood by the students to learn the concept of concept of conservation of area is recomposing shape. In recomposing shape, the students will see the fact that the shape can be transformed into a different form without adding or losing the part of the shape. So the students could conclude that the area of the shape before and after recomposing remains the same. Therefore, this study will answer how the students understand the initial idea (recomposing shape) of the concept of conservation of area. The instructional activity which was made in this study is based on realistic mathematics education. The activity was created for third grade elementary school students in SD Al-Hikmah Surabaya. The third grade students were used since they have not learned about area measurement. So they could focus just on the shape without disturbance of the area formula. The result of this study suggest that students still need more similar activities to ensure their understanding toward the idea that recomposing shape will preserve the area of the shape.Keywords: concept of conservation of area, initial understanding, recomposing shape